Assessment of air quality in preschool environments (3–5 years old children) with emphasis on elemental composition of PM10 and PM2.5. (July 2016) - Oliveira, Marta; Slezakova, Klara; Delerue-Matos, Cristina; Pereira, Maria Carmo; Morais, Simone
Abstract: This study evaluated concentrations of main air pollutants in a Portuguese preschool (indoors/outdoors) environment, with emphasis on elemental characterization of different PM fractions, and estimated risks for the pupils (aged 3–5 years). With exception to total volatile organic compounds, levels of PM10, PM2.5, CO, CO2, and formaldehyde were below legislative guidelines. Calcium, sodium, aluminium, and potassium were the most abundant elements in indoor PM (82–84% of the analysed content) resulting mainly from crustal sources. Carcinogenic elements (1–2% of the indoor analysed content) were mostly PM2.5 -bound (83–91%). Indoor-to-outdoor ratios of individual elements indicated contributions of indoor origin and from penetration of outdoor emissions indoors; trace metals were associated with ambient anthropogenic emissions (namely traffic). Non-carcinogenic and carcinogenic risks from overall preschool exposure were acceptable for children; for adults carcinogenic risks exceeded (4–11 times) the USEPA recommend value of 10 −6, being 8–40 times higher than for children. Highlights: Except for TVOCs, indoor CO2, PM2.5, PM10, CO and HCHO are below current guidelines. Ca, Na, Al, K are the most abundant PM elements and result from crustal sources. Carcinogenic elements (As, Cr, Ni, Cd, and Pb) are predominantly found in PM2.5 . Trace metals indicate contribution of ambient anthropogenic emissions to indoors. Carcinogenic risks due to indoor preschool exposure are higher than for outdoors. Abstract : Present study reports elemental characterization of fine and coarse PM in preschool environments, and assesses the respective risks.